Anti-corrosion magnesium alloy and preparation method and micro-arc oxidation treatment process thereof
By introducing rare earth elements into magnesium alloy and adopting microarc oxidation treatment process to form a ceramic film layer, the problem of magnesium alloy being easily corroded in humid environments is solved, and its corrosion resistance is significantly improved.
Patent Information
- Application Number
- CN202411578581.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-07
AI Technical Summary
Magnesium alloys are prone to galvanic corrosion in humid or high-salt environments, resulting in material failure, seriously affecting its structural safety and service life. The existing technology still has shortcomings in improving the corrosion resistance of magnesium alloys.
By optimizing the alloy composition, rare earth elements (lanthanum, samarium, gadolinium, yttrium) were introduced to significantly refine the grains of magnesium alloys, and a ceramic film layer was prepared through a microarc oxidation treatment process to form a uniform and dense protective layer.
The corrosion resistance of magnesium alloy is significantly improved. The corrosion rate of anti-corrosion magnesium alloy after soaking in 3.5wt.% sodium chloride solution for 72 hours has dropped to 0.10~0.15mg·cm-2·d-1, compared with the untreated Magnesium alloys have significantly improved.
Smart Images

Figure BDA0005122429420000131 
Figure BDA0005122429420000171 
Figure BDA0005122429420000181
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnesium alloys, and in particular to an anti-corrosion magnesium alloy and a preparation method and a micro-arc oxidation treatment process thereof. Background Art
[0002] Magnesium alloys have the advantages of low density, high specific strength, good electrical and thermal conductivity, good damping and vibration reduction, and recyclability. They are favored in aerospace, electronic communications, automobile manufacturing, biomedicine, and energy. However, their inherent low corrosion resistance has become the main obstacle to their widespread application. Magnesium alloys are prone to galvanic corrosion in humid or high-salt environments, leading to material failure and seriously affecting their structural safety and service life. With the increasing demand for lightweight materials, it is particularly important to improve the corrosion resistance of magnesium alloys.
[0003] At present, there are two main methods to improve the corrosion resistance of magnesium alloys. One method is to optimize the alloy composition and improve the corrosion resistance of the magnesium alloy itself. Chinese patent document CN117587308A discloses a corrosion-resistant magnesium alloy for marine atmospheric environment and its preparation method. By adding a combination of Y, Zn, Mn, and Sr elements to alloy the magnesium-aluminum alloy, the microgalvanic corrosion of the magnesium alloy is suppressed, the protective ability of the surface film is improved, and the corrosion resistance of the magnesium-aluminum alloy in the marine atmospheric environment is increased. The corrosion rate of the magnesium alloy material prepared by the patent in 3.5% NaCl aqueous solution for 5 days is 1.58-1.96 mg·cm -2 ·d -1 Chinese patent document CN118166251A discloses a corrosion-resistant magnesium alloy and its preparation method and application. The Ca element in the corrosion-resistant magnesium alloy can refine the grains, improve the mechanical properties and corrosion resistance. When the calcium content is 0.2-0.5wt%, the grain refining effect of Ca is significant. The corrosion rate of the magnesium alloy immersed in 0.9wt% NaCl solution for 15 days is ≤0.66mg·cm -2 ·d -1 The corrosion-resistant magnesium alloys disclosed in the above two patents have improved corrosion resistance to a certain extent compared with conventional magnesium alloys. However, for environments with higher requirements, the corrosion resistance of magnesium alloys needs to be further improved.
[0004] Another method to improve the corrosion resistance of magnesium alloys is to generate a protective layer of a certain thickness on the alloy surface through surface treatment technology, and use the surface protective layer to isolate the substrate from the corrosive medium to improve the corrosion resistance of magnesium alloys. Chinese patent document CN116770390A discloses a method for preparing a magnesium alloy micro-arc oxidation self-repairing coating, the electrolyte composition is: 15~20g·L -1 Na 2 SiO 3 10~15g·L -1KOH, 5~10g·L -1 KF, 4~9g·L -1 PEG-6000 and 2~7g·L -1 The modified halloysite nanotube powder, the micro-arc oxidation electrical parameters are: voltage 400 ~ 600V, current 3 ~ 5A dm -2 , duty cycle is 30-50%, frequency is 400-600Hz. Chinese patent document CN116607192A discloses a method for preparing a corrosion-resistant and wear-resistant coating of an ultra-low porosity magnesium alloy by micro-arc oxidation. The electrolyte composition is: 1-40g / L of a main film-forming agent (potassium dihydrogen phosphate or sodium dihydrogen phosphate), 1-30g / L of an auxiliary film-forming agent (sodium fluoride or potassium fluoride) and 1-20g / L of an additive (potassium fluorotitanate or potassium fluorozirconate or potassium fluorosilicate). The micro-arc oxidation electrical parameters are: current density is 0.1-10A / dm 2 , voltage is 300V~600V, frequency is 200~1000Hz, and duty cycle is 30~60%. The preparation methods of micro-arc oxidation coating disclosed in the above two patents have high electrolyte concentration and electrical parameter values, high preparation cost, and are not conducive to industrial application.
[0005] Based on existing technologies, by combining the optimization of alloy composition with the micro-arc oxidation surface treatment process, the corrosion resistance of magnesium alloys can be further improved, broadening their application prospects in aerospace, automobile, electronics and other fields, and promoting the development of lightweight and high-performance materials. Summary of the invention
[0006] In order to solve the problem of poor corrosion resistance of magnesium alloys in the prior art, the present invention provides an anti-corrosion magnesium alloy and a preparation method and a micro-arc oxidation treatment process thereof.
[0007] A corrosion-resistant magnesium alloy, the chemical composition of which is as follows by mass percentage: 4-8wt% aluminum, 2-5wt% lanthanum, 1-3wt% samarium, 0.5-1.0wt% gadolinium, 0.3-0.6wt% yttrium, 0.2-0.5wt% manganese, and the balance is magnesium and unavoidable impurities;
[0008] The total mass fraction of the unavoidable impurities is less than 0.03%.
[0009] A method for preparing the above-mentioned corrosion-resistant magnesium alloy is characterized by comprising the following steps:
[0010] Mg ingots, Al ingots, Mg-La master alloys, Mg-Sm master alloys, Mg-Gd master alloys, Mg-Y master alloys, and Mg-Mn master alloys were weighed according to the mass percentage of the alloy components, and then the Mg ingots, Al ingots, Mg-Gd master alloys, and Mg-Y master alloys were placed in a crucible furnace and SF 6 and CO2 Mixing protective gas, after the Mg ingot, Al ingot, Mg-Gd master alloy, and Mg-Y master alloy are completely melted, continuing to heat the crucible furnace, and adding Mg-La master alloy, Mg-Sm master alloy, and Mg-Mn master alloy, after the Mg-La master alloy, Mg-Sm master alloy, and Mg-Mn master alloy are completely melted, stirring, and then removing slag, after removing slag, cooling the crucible furnace, and casting the melt after standing to obtain Mg-Al-RE-Mn alloy;
[0011] Further, the crucible furnace continues to heat up to 710-730° C.;
[0012] Furthermore, the stirring time is 5 to 10 minutes;
[0013] Further, the crucible furnace is cooled down to 680-700°C;
[0014] Furthermore, the melt is allowed to stand for 30 minutes.
[0015] A micro-arc oxidation treatment process for the above-mentioned anti-corrosion magnesium alloy is characterized by comprising the following steps:
[0016] The Mg-Al-RE-Mn alloy sample was cut and firstly polished with metallographic sandpaper of 600#, 800#, 1000# and 2000#, then washed with deionized water and dried with cold air; 12-18g / L Na 2 SiO 3 , 3-7 g / L KF, 4-8 g / L KOH, and 5-15 ml / L propylene glycol are dissolved in deionized water to prepare an electrolyte; a Mg-Al-RE-Mn alloy sample is immersed in the electrolyte, the Mg-Al-RE-Mn alloy sample is used as an anode, and a stainless steel plate is used as a cathode, and electrical parameters are set using a constant voltage control mode: voltage is 330-370 V, frequency is 400-600 Hz, and duty cycle is 8-12%; after the parameter setting is completed, micro-arc oxidation treatment is performed, the electrolyte temperature is controlled, and drying is performed after the micro-arc oxidation treatment is completed to obtain a micro-arc oxidation ceramic film layer;
[0017] Furthermore, the micro-arc oxidation treatment time is 20 minutes;
[0018] Furthermore, the electrolyte temperature is controlled at 20-30°C;
[0019] Furthermore, the drying temperature is 50°C;
[0020] Furthermore, the drying time is 60 minutes.
[0021] Compared with the prior art, the present invention solves the problem of poor corrosion resistance of magnesium alloys, and has the following specific beneficial effects:
[0022] 1. Optimize alloy composition: The corrosion-resistant magnesium alloy provided by the present invention introduces rare earth elements (lanthanum, samarium, gadolinium, and yttrium) to significantly refine the grains of the magnesium alloy, and a large amount of rare earth phases are distributed near the grain boundaries. Especially when the rare earth content is high, the rare earth phase completely surrounds the primary α-Mg grains, making the grains independent and hindering the corrosion between the α-Mg grains. Although the rare earth phase also serves as a corrosion cathode relative to the matrix magnesium phase, the potential difference between it and the matrix is small, so it has no obvious acceleration effect on the corrosion of the alloy, reduces the micro-galvanic corrosion effect, and improves the corrosion resistance of the magnesium alloy. The corrosion rate of the corrosion-resistant magnesium alloy after immersion in a 3.5wt.% sodium chloride solution for 72 hours is 0.35-0.45mg·cm -2 ·d -1 .
[0023] 2. Micro-arc oxidation treatment process: The present invention adopts a micro-arc oxidation treatment process to prepare a micro-arc oxidation ceramic film layer of a corrosion-resistant magnesium alloy. Low voltage, low duty cycle and low concentration electrolyte are used in the preparation process, so that the micro-arc oxidation reaction is more stable, the reaction intensity is reduced, and local ablation is not easy to occur; the film thickness is more uniform, the pore size and cracks of the micro-arc oxidation film are reduced, and the difficulty of corrosive media to erode the magnesium alloy matrix is increased, further improving the corrosion resistance of the corrosion-resistant magnesium alloy. The corrosion rate of the corrosion-resistant magnesium alloy after micro-arc oxidation treatment is 0.10-0.15 mg·cm after being immersed in a 3.5wt.% sodium chloride solution for 72 hours. -2 ·d -1 .
[0024] 3. Obvious economic benefits: The preparation method of the anti-corrosion magnesium alloy and the micro-arc oxidation treatment process provided by the present invention are simple to operate and low in cost. For example, a constant voltage control mode, low voltage and low duty cycle are adopted in the preparation process to save energy. At the same time, a low-concentration electrolyte is used to reduce costs, and it has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Scanning electron microscope image of the microstructure morphology of the corrosion-resistant magnesium alloy;
[0026] Figure 2 This is a scanning electron microscope image of the cross-sectional morphology of the micro-arc oxidation film;
[0027] Figure 3 This is a scanning electron microscope image of the surface morphology of the micro-arc oxidation film. DETAILED DESCRIPTION
[0028] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.
[0029] Example 1.
[0030] The present embodiment relates to a corrosion-resistant magnesium alloy, a preparation method thereof and a micro-arc oxidation treatment process. The chemical composition of the corrosion-resistant magnesium alloy is as follows by mass percentage: Al: 6%, La: 3.5%, Sm: 2%, Gd: 0.75%, Y: 0.45%, Mn: 0.35%, and the remainder is magnesium and inevitable impurities; wherein the total mass percentage of the inevitable impurities is less than 0.03%.
[0031] (1) Weigh Mg ingots, Al ingots, Mg-La master alloys, Mg-Sm master alloys, Mg-Gd master alloys, Mg-Y master alloys, and Mg-Mn master alloys according to the mass percentage of the alloy components, then put the Mg ingots, Al ingots, Mg-Gd master alloys, and Mg-Y master alloys into a crucible furnace, and introduce SF 6 and CO 2 Mix the protective gas, wait for the Mg ingot, Al ingot, Mg-Gd master alloy, Mg-Y master alloy to be completely melted, then continue to heat the crucible furnace to 720°C, add Mg-La master alloy, Mg-Sm master alloy, Mg-Mn master alloy, wait for the Mg-La master alloy, Mg-Sm master alloy, Mg-Mn master alloy to be completely melted, stir for 10 minutes, then remove the slag, after removing the slag, lower the crucible furnace temperature to 690°C, let the melt stand for 30 minutes and then cast to obtain Mg-Al-RE-Mn alloy. The Mg-Al-RE-Mn alloy sample was immersed in a 3.5wt.% sodium chloride solution for 72 hours, and its corrosion rate was 0.35mg·cm -2 ·d -1 .
[0032] (2) The above Mg-Al-RE-Mn alloy samples were cut and subjected to micro-arc oxidation treatment. First, the Mg-Al-RE-Mn alloy samples were polished using metallographic sandpaper with particle sizes of 600#, 800#, 1000# and 2000#, respectively, and then washed with deionized water and dried with cold air; 15 g / L Na 2 SiO 3, 5g / L KF, 6g / L KOH, 10ml / L propylene glycol were dissolved in deionized water to prepare the electrolyte; the Mg-Al-RE-Mn alloy sample was immersed in the electrolyte, the Mg-Al-RE-Mn alloy sample was used as the anode, the stainless steel plate was used as the cathode, and the electrical parameters were set using the constant voltage control mode: the voltage was 350V, the frequency was 500Hz, and the duty cycle was 10%; after the parameter setting, the micro-arc oxidation treatment was carried out for 20 minutes, the electrolyte temperature was controlled at 20-30°C, and after micro-arc oxidation, it was dried at 50°C for 60 minutes to obtain a micro-arc oxidation ceramic film layer with a thickness of 11.5μm. The Mg-Al-RE-Mn alloy sample after micro-arc oxidation was immersed in a 3.5wt.% sodium chloride solution for 72h, and its corrosion rate was 0.10mg·cm -2 ·d -1 .
[0033] Figure 1 This is a scanning electron microscope image of the microstructure of the corrosion-resistant magnesium alloy. It can be seen from the image that the corrosion-resistant magnesium alloy presents a uniform fine-grain structure, and areas rich in rare earth phases are clearly distributed near the grain boundaries, indicating that the addition of rare earth elements during the smelting process effectively promotes grain refinement. Figure 2 The scanning electron microscope image of the cross-section morphology of the micro-arc oxidation film layer shows the microstructure of the cross-section of the film layer. The film layer thickness is uniformly 11.5μm, showing good density. Figure 3 This is a scanning electron microscope image of the surface morphology of the micro-arc oxidation film. The honeycomb-shaped micropores are uniform in size and have a small number of cracks. This uniform film layer helps to effectively block the penetration of corrosive media, reduce the exposure of the magnesium alloy matrix, and further improve the corrosion resistance of the alloy.
[0034] Example 2.
[0035] The present embodiment relates to a corrosion-resistant magnesium alloy, a preparation method thereof and a micro-arc oxidation treatment process. The chemical composition of the corrosion-resistant magnesium alloy is as follows by mass percentage: Al: 6%, La: 5%, Sm: 1%, Gd: 0.75%, Y: 0.45%, Mn: 0.35%, and the remainder is magnesium and inevitable impurities; wherein the total mass percentage of the inevitable impurities is less than 0.03%.
[0036] (1) Weigh Mg ingots, Al ingots, Mg-La master alloys, Mg-Sm master alloys, Mg-Gd master alloys, Mg-Y master alloys, and Mg-Mn master alloys according to the mass percentage of the alloy components, then put the Mg ingots, Al ingots, Mg-Gd master alloys, and Mg-Y master alloys into a crucible furnace, and introduce SF 6 and CO 2The protective gas is mixed, and after the Mg ingot, the Al ingot, the Mg-Gd master alloy, and the Mg-Y master alloy are completely melted, the crucible furnace is further heated to 720°C, and Mg-La master alloy, Mg-Sm master alloy, and Mg-Mn master alloy are added. After the Mg-La master alloy, Mg-Sm master alloy, and Mg-Mn master alloy are completely melted, they are stirred for 10 minutes, and then slag is removed. After slag removal, the temperature of the crucible furnace is lowered to 690°C, and the melt is allowed to stand for 30 minutes before casting to obtain a Mg-Al-RE-Mn alloy. The Mg-Al-RE-Mn alloy sample is immersed in a 3.5wt.% sodium chloride solution for 72 hours, and its corrosion rate is 0.4mg·cm -2 ·d -1 .
[0037] (2) The preparation steps and conditions are the same as those in Example 1 (2), and the thickness of the micro-arc oxidation ceramic film is 10.9 μm. The Mg-Al-RE-Mn alloy sample after micro-arc oxidation is immersed in a 3.5 wt.% sodium chloride solution for 72 h, and its corrosion rate is 0.12 mg·cm -2 ·d -1 .
[0038] Example 3.
[0039] The present embodiment relates to a corrosion-resistant magnesium alloy, a preparation method thereof, and a micro-arc oxidation treatment process. The chemical composition of the corrosion-resistant magnesium alloy is as follows by mass percentage: Al: 6%, La: 2%, Sm: 3%, Gd: 0.75%, Y: 0.45%, Mn: 0.35%, and the remainder is magnesium and inevitable impurities; wherein the total mass percentage of the inevitable impurities is less than 0.03%.
[0040] (1) Weigh Mg ingots, Al ingots, Mg-La master alloys, Mg-Sm master alloys, Mg-Gd master alloys, Mg-Y master alloys, and Mg-Mn master alloys according to the mass percentage of the alloy components, then put the Mg ingots, Al ingots, Mg-Gd master alloys, and Mg-Y master alloys into a crucible furnace, and introduce SF 6 and CO 2The protective gas is mixed, and after the Mg ingot, the Al ingot, the Mg-Gd master alloy, and the Mg-Y master alloy are completely melted, the crucible furnace is further heated to 720°C, and Mg-La master alloy, Mg-Sm master alloy, and Mg-Mn master alloy are added. After the Mg-La master alloy, Mg-Sm master alloy, and Mg-Mn master alloy are completely melted, they are stirred for 10 minutes, and then slag is removed. After slag removal, the temperature of the crucible furnace is lowered to 690°C, and the melt is allowed to stand for 30 minutes before casting to obtain a Mg-Al-RE-Mn alloy. The Mg-Al-RE-Mn alloy sample is immersed in a 3.5wt.% sodium chloride solution for 72 hours, and its corrosion rate is 0.42mg·cm -2 ·d -1 .
[0041] (2) The preparation steps and conditions are the same as those in Example 1 (2), and the thickness of the micro-arc oxidation ceramic film is 11.0 μm. The Mg-Al-RE-Mn alloy sample after micro-arc oxidation is immersed in a 3.5 wt.% sodium chloride solution for 72 h, and its corrosion rate is 0.13 mg·cm -2 ·d -1 .
[0042] Example 4.
[0043] The present embodiment relates to a corrosion-resistant magnesium alloy, a preparation method thereof and a micro-arc oxidation treatment process. The chemical composition of the corrosion-resistant magnesium alloy is as follows by mass percentage: Al: 6%, La: 3.5%, Sm: 2%, Gd: 0.75%, Y: 0.45%, Mn: 0.35%, and the remainder is magnesium and inevitable impurities; wherein the total mass percentage of the inevitable impurities is less than 0.03%.
[0044] (1) The Mg-Al-RE-Mn alloy sample was immersed in a 3.5 wt.% sodium chloride solution for 72 h under the same preparation steps and conditions as those in Example 1 (1). The corrosion rate was 0.35 mg·cm -2 ·d -1 .
[0045] (2) The above Mg-Al-RE-Mn alloy samples were cut and subjected to micro-arc oxidation treatment. First, the Mg-Al-RE-Mn alloy samples were polished using metallographic sandpaper with particle sizes of 600#, 800#, 1000# and 2000#, respectively, and then washed with deionized water and dried with cold air; 18 g / L Na 2 SiO 3, 3g / L KF, 4g / L KOH, 10ml / L propylene glycol were dissolved in deionized water to prepare the electrolyte; the Mg-Al-RE-Mn alloy sample was immersed in the electrolyte, the Mg-Al-RE-Mn alloy sample was used as the anode, the stainless steel plate was used as the cathode, and the electrical parameters were set using the constant voltage control mode: the voltage was 350V, the frequency was 500Hz, and the duty cycle was 10%; after the parameter setting, the micro-arc oxidation treatment was carried out for 20 minutes, the electrolyte temperature was controlled at 20-30℃, and after micro-arc oxidation, it was dried at 50℃ for 60 minutes to obtain a micro-arc oxidation ceramic film layer with a thickness of 11.2μm. The Mg-Al-RE-Mn alloy sample after micro-arc oxidation was immersed in a 3.5wt.% sodium chloride solution for 72h, and its corrosion rate was 0.11mg·cm -2 ·d -1 .
[0046] Example 5.
[0047] The present embodiment relates to a corrosion-resistant magnesium alloy, a preparation method thereof and a micro-arc oxidation treatment process. The chemical composition of the corrosion-resistant magnesium alloy is as follows by mass percentage: Al: 6%, La: 3.5%, Sm: 2%, Gd: 0.75%, Y: 0.45%, Mn: 0.35%, and the remainder is magnesium and inevitable impurities; wherein the total mass percentage of the inevitable impurities is less than 0.03%.
[0048] (1) The Mg-Al-RE-Mn alloy sample was immersed in a 3.5 wt.% sodium chloride solution for 72 h under the same preparation steps and conditions as those in Example 1 (1). The corrosion rate was 0.38 mg·cm -2 ·d -1 .
[0049] (2) The above Mg-Al-RE-Mn alloy samples were cut and subjected to micro-arc oxidation treatment. First, the Mg-Al-RE-Mn alloy samples were polished using metallographic sandpaper with particle sizes of 600#, 800#, 1000# and 2000#, respectively, and then washed with deionized water and dried with cold air; 12 g / L Na 2 SiO 3, 7g / L KF, 8g / L KOH, 10ml / L propylene glycol were dissolved in deionized water to prepare the electrolyte; the Mg-Al-RE-Mn alloy sample was immersed in the electrolyte, the Mg-Al-RE-Mn alloy sample was used as the anode, the stainless steel plate was used as the cathode, and the electrical parameters were set using the constant voltage control mode: the voltage was 350V, the frequency was 500Hz, and the duty cycle was 10%; after the parameter setting, the micro-arc oxidation treatment was carried out for 20 minutes, the electrolyte temperature was controlled at 20-30℃, and after micro-arc oxidation, it was dried at 50℃ for 60 minutes to obtain a micro-arc oxidation ceramic film layer with a thickness of 10.6μm. The Mg-Al-RE-Mn alloy sample after micro-arc oxidation was immersed in a 3.5wt.% sodium chloride solution for 72h, and its corrosion rate was 0.15mg·cm -2 ·d -1 .
[0050] Example 6.
[0051] The present embodiment relates to a corrosion-resistant magnesium alloy, a preparation method thereof and a micro-arc oxidation treatment process. The chemical composition of the corrosion-resistant magnesium alloy is as follows by mass percentage: Al: 6%, La: 3.5%, Sm: 2%, Gd: 0.75%, Y: 0.45%, Mn: 0.35%, and the remainder is magnesium and inevitable impurities; wherein the total mass percentage of the inevitable impurities is less than 0.03%.
[0052] (1) The Mg-Al-RE-Mn alloy sample was immersed in a 3.5 wt.% sodium chloride solution for 72 h under the same preparation steps and conditions as those in Example 1. The corrosion rate was 0.36 mg·cm -2 ·d -1 .
[0053] (2) The above Mg-Al-RE-Mn alloy samples were cut and subjected to micro-arc oxidation treatment. First, the Mg-Al-RE-Mn alloy samples were polished using metallographic sandpaper with particle sizes of 600#, 800#, 1000# and 2000#, respectively, and then washed with deionized water and dried with cold air; 18 g / L Na 2 SiO 37g / L KF, 8g / L KOH, and 15ml / L propylene glycol were dissolved in deionized water to prepare an electrolyte; the Mg-Al-RE-Mn alloy sample was immersed in the electrolyte, the Mg-Al-RE-Mn alloy sample was used as the anode, the stainless steel plate was used as the cathode, and the electrical parameters were set using the constant voltage control mode: the voltage was 350V, the frequency was 500Hz, and the duty cycle was 10%; after the parameter setting was completed, the micro-arc oxidation treatment was carried out for 20 minutes, the electrolyte temperature was controlled at 20-30°C, and after micro-arc oxidation, it was dried at 50°C for 60 minutes to obtain a micro-arc oxidation ceramic film layer with a thickness of 11.3μm. The Mg-Al-RE-Mn alloy sample after micro-arc oxidation was immersed in a 3.5wt.% sodium chloride solution for 72h, and its corrosion rate was 0.13mg·cm -2 ·d -1 .
[0054] Example 7.
[0055] The present embodiment relates to a corrosion-resistant magnesium alloy, a preparation method thereof and a micro-arc oxidation treatment process. The chemical composition of the corrosion-resistant magnesium alloy is as follows by mass percentage: Al: 6%, La: 3.5%, Sm: 2%, Gd: 0.75%, Y: 0.45%, Mn: 0.35%, and the remainder is magnesium and inevitable impurities; wherein the total mass percentage of the inevitable impurities is less than 0.03%.
[0056] (1) The Mg-Al-RE-Mn alloy sample was immersed in a 3.5 wt.% sodium chloride solution for 72 h under the same preparation steps and conditions as those in Example 1 (1). The corrosion rate was 0.38 mg·cm -2 ·d -1 .
[0057] (2) The above Mg-Al-RE-Mn alloy samples were cut and subjected to micro-arc oxidation treatment. First, the Mg-Al-RE-Mn alloy samples were polished using metallographic sandpaper with particle sizes of 600#, 800#, 1000# and 2000#, respectively, and then washed with deionized water and dried with cold air; 15 g / L Na 2 SiO 3, 5g / L KF, 6g / L KOH, and 10ml / L propylene glycol were dissolved in deionized water to prepare an electrolyte; the Mg-Al-RE-Mn alloy sample was immersed in the electrolyte, the Mg-Al-RE-Mn alloy sample was used as the anode, and the stainless steel plate was used as the cathode. The electrical parameters were set in a constant voltage control mode: the voltage was 370V, the frequency was 500Hz, and the duty cycle was 8%; after the parameter setting was completed, micro-arc oxidation treatment was carried out for 20 minutes, the electrolyte temperature was controlled at 20-30°C, and after micro-arc oxidation, it was dried at 50°C for 60 minutes to obtain a micro-arc oxidation ceramic film layer with a thickness of 11.2μm. The Mg-Al-RE-Mn alloy sample after micro-arc oxidation was immersed in a 3.5wt.% sodium chloride solution for 72h, and its corrosion rate was 0.12mg·cm -2 ·d -1 .
[0058] Example 8.
[0059] The present embodiment relates to a corrosion-resistant magnesium alloy, a preparation method thereof and a micro-arc oxidation treatment process. The chemical composition of the corrosion-resistant magnesium alloy is as follows by mass percentage: Al: 6%, La: 3.5%, Sm: 2%, Gd: 0.75%, Y: 0.45%, Mn: 0.35%, and the remainder is magnesium and inevitable impurities; wherein the total mass percentage of the inevitable impurities is less than 0.03%.
[0060] (1) The Mg-Al-RE-Mn alloy sample was immersed in a 3.5 wt.% sodium chloride solution for 72 h under the same preparation steps and conditions as those in Example 1. The corrosion rate was 0.37 mg·cm -2 ·d -1 .
[0061] (2) The above Mg-Al-RE-Mn alloy samples were cut and subjected to micro-arc oxidation treatment. First, the Mg-Al-RE-Mn alloy samples were polished using metallographic sandpaper with particle sizes of 600#, 800#, 1000# and 2000#, respectively, and then washed with deionized water and dried with cold air; 15 g / L Na 2 SiO 3, 5g / L KF, 6g / L KOH, 10ml / L propylene glycol were dissolved in deionized water to prepare the electrolyte; the Mg-Al-RE-Mn alloy sample was immersed in the electrolyte, the Mg-Al-RE-Mn alloy sample was used as the anode, the stainless steel plate was used as the cathode, and the electrical parameters were set using the constant voltage control mode: the voltage was 330V, the frequency was 500Hz, and the duty cycle was 12%; after the parameter setting, the micro-arc oxidation treatment was carried out for 20 minutes, the electrolyte temperature was controlled at 20-30℃, and after micro-arc oxidation, it was dried at 50℃ for 60 minutes to obtain a micro-arc oxidation ceramic film layer with a thickness of 10.7μm. The Mg-Al-RE-Mn alloy sample after micro-arc oxidation was immersed in a 3.5wt.% sodium chloride solution for 72h, and its corrosion rate was 0.15mg·cm -2 ·d -1 .
[0062] According to the Mg-Al-RE-Mn alloys prepared in Examples 1-8, Table 1 shows the corrosion rates of the Mg-Al-RE-Mn alloy samples before and after micro-arc oxidation treatment.
[0063] Table 1
[0064]
[0065] Comparative Example 1.
[0066] The present comparative example relates to a corrosion-resistant magnesium alloy, a preparation method thereof and a micro-arc oxidation treatment process. The chemical composition of the corrosion-resistant magnesium alloy is as follows by mass percentage: Al: 6%, La: 1.5%, Sm: 0.5%, Gd: 0.75%, Y: 0.45%, Mn: 0.35%, and the remainder is magnesium and inevitable impurities; wherein the total mass percentage of the inevitable impurities is less than 0.03%.
[0067] (1) Weigh Mg ingots, Al ingots, Mg-La master alloys, Mg-Sm master alloys, Mg-Gd master alloys, Mg-Y master alloys, and Mg-Mn master alloys according to the mass percentage of the alloy components, then put the Mg ingots, Al ingots, Mg-Gd master alloys, and Mg-Y master alloys into a crucible furnace, and introduce SF 6 and CO 2Mix the protective gas, wait for the Mg ingot, Al ingot, Mg-Gd master alloy, Mg-Y master alloy to be completely melted, then continue to heat the crucible furnace to 720°C, add Mg-La master alloy, Mg-Sm master alloy, Mg-Mn master alloy, wait for the Mg-La master alloy, Mg-Sm master alloy, Mg-Mn master alloy to be completely melted, stir for 10 minutes, then remove the slag, after removing the slag, lower the crucible furnace temperature to 690°C, let the melt stand for 30 minutes and then cast to obtain Mg-Al-RE-Mn alloy. The Mg-Al-RE-Mn alloy sample was immersed in a 3.5wt.% sodium chloride solution for 72 hours, and its corrosion rate was 1.29mg·cm -2 ·d -1 .
[0068] (2) The preparation steps and conditions are the same as those in Example 1 (2), and the thickness of the micro-arc oxidation ceramic film is 10.9 μm. The Mg-Al-RE-Mn alloy sample after micro-arc oxidation is immersed in a 3.5 wt.% sodium chloride solution for 72 h, and its corrosion rate is 0.42 mg·cm -2 ·d -1 .
[0069] The main difference between this comparative example and Example 1 is that the contents of the alloy components La and Sm in step (1) are reduced, the rare earth phase is reduced, and the corrosion resistance of the Mg-Al-RE-Mn alloy sample is reduced compared with Example 1.
[0070] Comparative Example 2.
[0071] The present comparative example relates to a corrosion-resistant magnesium alloy, a preparation method thereof and a micro-arc oxidation treatment process. The chemical composition of the corrosion-resistant magnesium alloy is as follows by mass percentage: Al: 6%, La: 3.5%, Sm: 2%, Gd: 0.75%, Y: 0.45%, Mn: 0.35%, and the remainder is magnesium and inevitable impurities; wherein the total mass percentage of the inevitable impurities is less than 0.03%.
[0072] (1) The Mg-Al-RE-Mn alloy sample was immersed in a 3.5 wt.% sodium chloride solution for 72 h under the same preparation steps and conditions as those in Example 1 (1). The corrosion rate was 0.40 mg·cm -2 ·d -1 .
[0073] (2) The above Mg-Al-RE-Mn alloy samples were cut and subjected to micro-arc oxidation treatment. First, the Mg-Al-RE-Mn alloy samples were polished using metallographic sandpaper with particle sizes of 600#, 800#, 1000# and 2000#, respectively, and then washed with deionized water and dried with cold air; 8 g / L Na 2 SiO3 , 2g / L KF, 3g / L KOH, 10ml / L propylene glycol were dissolved in deionized water to prepare the electrolyte; the Mg-Al-RE-Mn alloy sample was immersed in the electrolyte, the Mg-Al-RE-Mn alloy sample was used as the anode, the stainless steel plate was used as the cathode, and the electrical parameters were set using the constant voltage control mode: the voltage was 350V, the frequency was 500Hz, and the duty cycle was 10%; after the parameter setting, the micro-arc oxidation treatment was carried out for 20 minutes, the electrolyte temperature was controlled at 20-30℃, and after micro-arc oxidation, it was dried at 50℃ for 60 minutes to obtain a micro-arc oxidation ceramic film layer with a thickness of 7.8μm. The Mg-Al-RE-Mn alloy sample after micro-arc oxidation was immersed in a 3.5wt.% sodium chloride solution for 72h, and its corrosion rate was 0.29mg·cm -2 ·d -1 .
[0074] The main difference between this comparative example and Example 1 is that the electrolyte component Na in step (2) 2 SiO 3 , KF and KOH concentrations decreased, the number of ions participating in the micro-arc oxidation reaction decreased, the conductivity of the electrolyte decreased, and the thickness of the film layer decreased, resulting in the corrosion resistance of the Mg-Al-RE-Mn alloy sample after micro-arc oxidation treatment being lower than that in Example 1.
[0075] Comparative Example 3.
[0076] The present comparative example relates to a corrosion-resistant magnesium alloy, a preparation method thereof and a micro-arc oxidation treatment process. The chemical composition of the corrosion-resistant magnesium alloy is as follows by mass percentage: Al: 6%, La: 3.5%, Sm: 2%, Gd: 0.75%, Y: 0.45%, Mn: 0.35%, and the remainder is magnesium and inevitable impurities; wherein the total mass percentage of the inevitable impurities is less than 0.03%.
[0077] (1) The Mg-Al-RE-Mn alloy sample was immersed in a 3.5 wt.% sodium chloride solution for 72 h under the same preparation steps and conditions as those in Example 1 (1). The corrosion rate was 0.38 mg·cm -2 ·d -1 .
[0078] (2) The above Mg-Al-RE-Mn alloy samples were cut and subjected to micro-arc oxidation treatment. First, the Mg-Al-RE-Mn alloy samples were polished using metallographic sandpaper with particle sizes of 600#, 800#, 1000# and 2000#, respectively, and then washed with deionized water and dried with cold air; 15 g / L Na 2 SiO 3, 5g / L KF, 6g / L KOH, 10ml / L propylene glycol were dissolved in deionized water to prepare the electrolyte; the Mg-Al-RE-Mn alloy sample was immersed in the electrolyte, the Mg-Al-RE-Mn alloy sample was used as the anode, the stainless steel plate was used as the cathode, and the electrical parameters were set using the constant voltage control mode: the voltage was 300V, the frequency was 500Hz, and the duty cycle was 6%; after the parameter setting, the micro-arc oxidation treatment was carried out for 20 minutes, the electrolyte temperature was controlled at 20-30℃, and after micro-arc oxidation, it was dried at 50℃ for 60 minutes to obtain a micro-arc oxidation ceramic film layer with a thickness of 6.5μm. The Mg-Al-RE-Mn alloy sample after micro-arc oxidation was immersed in a 3.5wt.% sodium chloride solution for 72h, and its corrosion rate was 0.31mg·cm -2 ·d -1 .
[0079] The main difference between this comparative example and Example 1 is that the electrical parameter voltage and duty cycle in step (2) are reduced, resulting in a reduction in the energy provided to the micro-arc oxidation reaction, a reduction in the film growth rate, and a reduction in the film thickness. Finally, the corrosion resistance of the Mg-Al-RE-Mn alloy sample after micro-arc oxidation treatment is reduced compared with that in Example 1.
[0080] Comparative Example 4.
[0081] The corrosion rate of AM60 magnesium alloy after immersion in 3.5wt.% sodium chloride solution for 72h was 2.31mg·cm -2 ·d -1 .
[0082] AM60 magnesium alloy was subjected to micro-arc oxidation treatment. First, AM60 magnesium alloy was polished with metallographic sandpapers of 600#, 800#, 1000# and 2000#, then washed with deionized water and dried with cold air. 15g / L Na 2 SiO 3 , 5g / L KF, 6g / L KOH, 10ml / L propylene glycol are dissolved in deionized water to prepare the electrolyte; the AM60 magnesium alloy is immersed in the electrolyte, the AM60 magnesium alloy is used as the anode, the stainless steel plate is used as the cathode, and the electrical parameters are set using the constant voltage control mode: the voltage is 350V, the frequency is 500Hz, and the duty cycle is 10%; after the parameter setting is completed, the micro-arc oxidation treatment is carried out for 20 minutes, the electrolyte temperature is controlled at 20-30℃, and after micro-arc oxidation, it is dried at 50℃ for 60 minutes to obtain a micro-arc oxidation ceramic film layer with a thickness of 11.3μm. The AM60 magnesium alloy after micro-arc oxidation is immersed in a 3.5wt.% sodium chloride solution for 72h, and its corrosion rate is 0.78mg·cm -2 ·d -1 .
[0083] Since AM60 magnesium alloy does not contain rare earth elements, microgalvanic corrosion occurs in the sample immersion test before micro-arc oxidation treatment, resulting in a corrosion rate of 2.31 mg cm-1 for AM60 magnesium alloy before micro-arc oxidation treatment. -2 ·d -1 , the corrosion rate of AM60 magnesium alloy after micro-arc oxidation treatment is still higher than that of Mg-Al-RE-Mn alloy prepared in Example 1. Table 2 below shows the corrosion rates of magnesium alloy samples in Comparative Examples 1-4 before and after micro-arc oxidation treatment.
[0084] Table 2
[0085]
[0086]
[0087] The corrosion-resistant magnesium alloy provided by the present invention introduces rare earth elements (lanthanum, samarium, gadolinium, and yttrium) to significantly refine the grains of the magnesium alloy, and a large amount of rare earth phases are distributed near the grain boundaries. Especially when the rare earth content is high, the rare earth phases completely surround the primary α-Mg grains, making the grains independent, hindering the corrosion between the α-Mg grains, and improving the corrosion resistance of the magnesium alloy. The corrosion rate of the corrosion-resistant magnesium alloy after being immersed in a 3.5wt.% sodium chloride solution for 72 hours is 0.35-0.45mg·cm -2 ·d -1 . The micro-arc oxidation ceramic film layer of the corrosion-resistant magnesium alloy was prepared by the micro-arc oxidation treatment process. Low voltage, low duty cycle and low concentration electrolyte were used in the preparation process, which made the micro-arc oxidation reaction more stable, reduced the intensity of the reaction, and less prone to local ablation. The film thickness was made more uniform, the pore size and cracks of the micro-arc oxidation film were reduced, and the difficulty of corrosive media eroding the magnesium alloy matrix was increased, further improving the corrosion resistance of the corrosion-resistant magnesium alloy. The corrosion rate of the corrosion-resistant magnesium alloy after micro-arc oxidation treatment was 0.10-0.15 mg·cm after being immersed in 3.5wt.% sodium chloride solution for 72 hours. -2 ·d -1 .
Claims
1. A corrosion-resistant magnesium alloy, characterized in that: Its chemical composition by mass percentage is: 4-8wt% aluminum, 2-5wt% lanthanum, 1-3wt% samarium, 0.5-1.0wt% gadolinium, 0.3-0.6wt% yttrium, 0.2-0.5wt% manganese, and the balance is magnesium and unavoidable impurities; The total mass fraction of the unavoidable impurities is less than 0.03%.
2. A method for preparing the corrosion-resistant magnesium alloy according to claim 1, characterized in that: The following steps are involved: Mg ingots, Al ingots, Mg-La master alloys, Mg-Sm master alloys, Mg-Gd master alloys, Mg-Y master alloys and Mg-Mn master alloys are weighed according to the mass percentage of the alloy components, and then the Mg ingots, Al ingots, Mg-Gd master alloys and Mg-Y master alloys are put into a crucible furnace, and a mixed protective gas of SF6 and CO2 is introduced. After the Mg ingots, Al ingots, Mg-Gd master alloys and Mg-Y master alloys are completely melted, the crucible furnace is heated up continuously, and Mg-La master alloys, Mg-Sm master alloys and Mg-Mn master alloys are added. After the Mg-La master alloys, Mg-Sm master alloys and Mg-Mn master alloys are completely melted, they are stirred, and then slag is removed. After slag removal, the crucible furnace is cooled down, and the melt is allowed to stand and then cast to obtain a Mg-Al-RE-Mn alloy.
3. The method for preparing the corrosion-resistant magnesium alloy according to claim 2, characterized in that: The crucible furnace continues to heat up to 710-730°C.
4. The method for preparing the corrosion-resistant magnesium alloy according to claim 2, characterized in that: The stirring time is 5 to 10 minutes.
5. The method for preparing the corrosion-resistant magnesium alloy according to claim 2, characterized in that: The crucible furnace is cooled down to 680-700°C.
6. The method for preparing the corrosion-resistant magnesium alloy according to claim 2, characterized in that: The melt resting time is 30 minutes.
7. A micro-arc oxidation process for a corrosion-resistant magnesium alloy prepared by the preparation method according to claim 1 or claims 2-6, characterized in that: The following steps are involved: A Mg-Al-RE-Mn alloy sample was cut, and firstly, it was polished with metallographic sandpaper with particle size specifications of 600#, 800#, 1000# and 2000# in sequence, and then it was washed with deionized water and dried with cold air; 12-18g / L Na2SiO3, 3-7g / LKF, 4-8g / L KOH, and 5-15ml / L propylene glycol were dissolved in deionized water to prepare an electrolyte; the Mg-Al-RE-Mn alloy sample was immersed in the electrolyte, the Mg-Al-RE-Mn alloy sample was used as an anode, and a stainless steel plate was used as a cathode, and electrical parameters were set using a constant voltage control mode: the voltage was 330-370V, the frequency was 400-600Hz, and the duty cycle was 8-12%; after the parameter setting was completed, a micro-arc oxidation treatment was carried out to control the electrolyte temperature, and after the micro-arc oxidation treatment was completed, it was dried to obtain a micro-arc oxidation ceramic film layer.
8. The micro-arc oxidation treatment process for corrosion-resistant magnesium alloy according to claim 7, characterized in that: The micro-arc oxidation treatment time is 20 minutes.
9. The micro-arc oxidation treatment process for corrosion-resistant magnesium alloy according to claim 7, characterized in that: The electrolyte temperature is controlled at 20-30°C.
10. The micro-arc oxidation treatment process for anti-corrosion magnesium alloy according to claim 7, characterized in that: The drying temperature is 50° C. and the drying time is 60 minutes.
Citation Information
Patent Citations
Preparation method of ultralow-porosity magnesium alloy micro-arc oxidation corrosion-resistant and wear-resistant coating
CN116607192A
Preparation method of magnesium alloy micro-arc oxidation self-repairing coating
CN116770390A
Corrosion-resistant magnesium alloy for marine atmospheric environment and preparation method of corrosion-resistant magnesium alloy
CN117587308A
Corrosion-resistant magnesium alloy as well as preparation method and application thereof
CN118166251A
Cited By
High-temperature-resistant creep-resistant die-casting magnesium alloy and preparation method thereof
CN121976100A